Qualidade de vida e saúde vocal de professores Quality of life and vocal health of teachers - Regina Zanella Penteado; Isabel Maria Teixeira Bicudo Pereira (Universidade de São Paulo, 2007)
OBJETIVO: Avaliar aspectos associados à qualidade de vida de professores e buscar relações com questões de saúde vocal. MÉTODOS: Foi estudada uma amostra de 128 professores de ensino médio de quatro escolas estaduais de Rio Claro, SP, em 2002. Foram aplicados os questionários World Health Organization Quality of Life/bref e Qualidade de Vida e Voz e calculados média e desvio-padrão para os escores do primeiro questionário e da questão de auto-avaliação vocal do questionário Qualidade de Vida e Voz. Utilizou-se o teste de Wilcoxon para comparar os gêneros; o de Kruskal-Wallis para as escolas; e o coeficiente de correlação de Spearman e teste t para verificar associação entre os domínios da qualidade de vida, a auto-avaliação vocal e idade, e número de períodos que o professor leciona. RESULTADOS: A maioria avaliou a voz como boa (42,2%) e o escore médio do questionário de avaliação de qualidade de vida foi 66, com maiores valores do domínio relações sociais e menores do meio ambiente. Os aspectos associados foram oportunidades de lazer, condições financeiras, ambiente de trabalho e acesso à informação. O número de períodos lecionados apresentou correlação positiva e significativa com a auto-avaliação vocal. Não houve diferença significativa entre os gêneros. Houve diferenças significativas no domínio físico, quando comparados os resultados das diferentes escolas. CONCLUSÕES: Apesar de razoavelmente satisfeitos com a voz e a qualidade de vida, os professores mostraram dificuldades na percepção do processo saúde-doença. Evidenciaram-se aspectos desfavorecidos da qualidade de vida e necessidades de saúde que podem ter implicações na voz e saúde vocal docente. OBJECTIVE: To evaluate aspects of teachers' quality of life and describe associated factors to their vocal health. METHODS: A sample comprising 128 high school teachers from four state schools in the city of Rio Claro, Southeastern Brazil, was studied in 2002. The World Health Organization Quality of Life/bref and Voice-Related Quality of Life questionnaires were applied and there were calculated the averages, standard deviation values for the first questionnaire scores and the self-evaluation question of the Voice-Related Quality of Life. The Wilcoxon's test was used to compare teachers' genders; the Kruskal-Wallis's test was used to compare schools and Spearman's correlation coefficient and t-test were performed to assess the association between the domains of quality of life, the vocal self-evaluation question and age, and the number of working shifts by a teacher. RESULTS: Most teachers evaluated their voice as good (42.2%) and the mean score of the quality of life questionnaire was 66, with the highest scores in the domain of social relations, and the lowest ones in the environment domain. The most affected aspects were leisure opportunities, financial conditions, work environment and access to information. The number of hours worked by a teacher had a positive significant correlation with vocal self-evaluation. There were no significant differences between genders. There were significant differences in the physical domain when comparing schools. CONCLUSIONS: Although teachers showed to be reasonably satisfied with their vocal and life quality, they showed misperceptions of their health disorder process and evidenced neglected aspects of life quality and health needs that may compromise teachers' voice/vocal health.